2008
DOI: 10.4161/auto.6691
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar p19ARF unlike mitochondrial smARF is incapable of inducing p53-independent autophagy

Abstract: ARF mRNA encodes two distinct proteins, the nucleolar p19 ARF , and a shorter mitochondrial isoform, named smARF. Inappropriate proliferative signals generated by proto-oncogenes, such as c-Myc and E2F1, can elevate both p19 ARF and smARF proteins. The two ARF isoforms differ not only in their localization but also in their functions. Nucleolar p19 ARF inhibits cell growth mainly by activating p53 or by inhibiting ribosomal biogenesis. In contrast, mitochondrial smARF can induce dissipation of the mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…As a result, cell lines overexpressing smARF are more sensitive to the induction of autophagy and senescence caused by starvation or hydrogen peroxide (Pimkina et al, 2009). In contrast, expression of nucleolar ARF does not confer a similar effect (Reef and Kimchi, 2008). These observations indicate that smARF may link autophagy to senescence but whether this applies also in response to DNA damage remains to be determined.…”
Section: Functional Outcomes Of the Ddr – Autophagy Axismentioning
confidence: 99%
“…As a result, cell lines overexpressing smARF are more sensitive to the induction of autophagy and senescence caused by starvation or hydrogen peroxide (Pimkina et al, 2009). In contrast, expression of nucleolar ARF does not confer a similar effect (Reef and Kimchi, 2008). These observations indicate that smARF may link autophagy to senescence but whether this applies also in response to DNA damage remains to be determined.…”
Section: Functional Outcomes Of the Ddr – Autophagy Axismentioning
confidence: 99%
“…The pro-autophagic effect of short mitochondrial ARF is known to be enhanced by the mitochondrial p32 protein that stabilizes short mitochondrial ARF but not the full-length ARF (Reef et al, 2007). It has been shown that the full-length ARF that normally resides in the nucleolus is incapable of inducing p53-independent autophagy (Reef and Kimchi, 2008).…”
Section: V12mentioning
confidence: 99%
“…66 Yet, a further detailed study established that nucleolar localized full-length p19ARF, unlike the mitochondrial smARF, is incapable of inducing p53-independent autophagy. 67 An additional study suggested that human p14ARF also localizes to the outer membrane of mitochondria where it binds Bcl-2/X L , thereby reducing the latter's association with Beclin 1, 68 although it is unclear how an interaction at the mitochondria affects the ER-localized Bcl-2/ Beclin 1 complex. Oncogene expression results in the induction of both full-length p19ARF and smARF, 64 suggesting that smARF's contribution to autophagy is more prominent upon specific cell signals.…”
Section: Cross-talk Between Autophagy and Apoptosismentioning
confidence: 99%